PERUBAHAN PERAN BATIN DI SUKU PETALANGAN (Studi Kasus Pebatinan Monti Raja Desa Betung) - Armilus, Robi; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research analyze the changes of Batin roles in Suku Petalangan in the case of Pebatinan Monti Raja Desa Betung. Batin role changes that occur in Petalangan tribe is a social phenomenon that occurs in the Petalangan, Batin position in view of the public in Petalangan Betung village has an important position. Batin is a leader for his people, where Batin has a role to educate people in inheritance, marriage, dispute, besides maintaining communal land and jungle siege beehive. But in fact the contemporary conditions with increasingly advanced technology and information on the inner part Petalangan rate changes. Batin no longer maximal in implementing the rights and obligations of the nephew and keep treasures that exist in the Petalangan. This research explained under framework of structural functional perspective, theory of change By Himes dan More. This research uses qualitative methode with library system of study and pusposive technique where the number of respondents amounted to 8 people consisting of traditional authorities of Batin Monti Raja. The research show that the role of the mind in Betung village Petalangan rate changes caused by internal and external factors, namely technology, education, economics, government intervention and contact with a foreign culture, the social impact of the order of values and culture Petalangan that with the loss of some ritual Petalangan customs.Keywords : Change, Roles, Batin Monti Raja, Petalangan trible